(untitled) (Delta Medical College Journal, 2020)
Background: Propofol, the most frequently used intravenous anaesthetic, is used for induction, maintenance of anaesthesia and for sedation in patients scheduled for routine elective surgical procedure. Pain on propofol injection still remains a considerable concern for the anaesthesiologist. Objective: Aim of this study was to observe the efficacy of metoclopramide as pretreatment for the prevention of pain caused by the propofol injection in patients undergoing elective surgery under general anaesthesia. Materials and method: A total of 80 patients were taken up in the study in the age group of 20 to 50 years of either sex, ASA grade I/II, scheduled for routine elective surgical procedure under general anesthesia with endotracheal intubation and using propofol as induction agent. The patients enrolled were divided randomly into two groups of 40 patients each. Group A received 10 mg metoclopramide IV diluted in 5 ml saline. Group B received 5 ml of normal saline as placebo before propofol injection. The patients were asked to report their pain according to the scale provided to them in the form of none, mild, moderate and severe after injection of propofol. Results: The overall incidence and severity of pain were significantly less in Group A (metoclopramide group) than in group B (placebo group) (p< 0.05). The incidence of mild and moderate pain in Group A versus group B was 15% vs 45% and 5% vs 25% respectively (p<0.05). The incidence of score ‘0’ (no pain) was higher in Group A (80%) thanGroup B (25%) (p< 0.05). Conclusion: Intravenous metoclopramide is effective for relief of pain on propofol injection without any significant side effects. Delta Med Col J. Jul 2019 7(2): 71-75